Magnetoelectrically Driven Catalytic Degradation of Organics. Issue 28 (2nd May 2019) - Mushtaq, Fajer; Chen, Xiangzhong; Torlakcik, Harun; Steuer, Christian; Hoop, Marcus; Siringil, Erdem Can; Marti, Xavi; Limburg, Gregory; Stipp, Patrick; Nelson, Bradley J.; Pané, Salvador
Abstract: Here, the catalytic degradation of organic compounds is reported by exploiting the magnetoelectric nature of cobalt ferrite–bismuth ferrite (CFO–BFO) core–shell nanoparticles. The combination of magnetostrictive CFO with multiferroic BFO gives rise to a magnetoelectric engine that purifies water under wireless magnetic fields via advanced oxidation processes, without involvement of any sacrificial molecules or cocatalysts. Magnetostrictive CoFe2 O4 nanoparticles are fabricated using hydrothermal synthesis, followed by sol–gel synthesis to create the multiferroic BiFeO3 shell. Theoretical modeling is performed to study the magnetic‐field‐induced polarization on the surface of magnetoelectric nanoparticles. The results obtained from these simulations are consistent with experimental findings of the piezoforce microscopy analysis, where changes in piezoresponse of the nanoparticles under magnetic fields are observed. Next, the magnetoelectric‐effect‐induced catalytic degradation of organic pollutants is investigated under AC magnetic fields, and 97% removal efficiency for synthetic dyes and over 85% removal efficiency for routinely used pharmaceuticals are obtained. Additionally, trapping experiments are performed to elucidate the mechanism behind the magnetic‐field‐induced catalytic degradation of organic pollutants by using scavengers for each of the reactive species. The results indicate that hydroxyl and superoxide radicals are the main reactive species in the magnetoelectrically induced catalytic degradation of organic compounds. Abstract : Organic compounds are degraded by the magnetoelectric (ME) nature of cobalt ferrite–bismuth ferrite (CFO–BFO) core–shell nanoparticles. The combination of the magnetostrictive CFO with the multiferroic BFO gives rise to a magnetoelectric engine that purifies water under wireless magnetic fields via advanced oxidation processes, without involvement of any sacrificial molecules or cocatalysts.